Hot planets around cool stars – two short-period mini-Neptunes transiting the late K-dwarf TOI-1260. Issue 4 (22nd May 2021) - Georgieva, I Y; Persson, C M; Barragán, O; Nowak, G; Fridlund, M; Locci, D; Palle, E; Luque, R; Carleo, I; Gandolfi, D; Kane, S R; Korth, J; et al.
ABSTRACT: We present the discovery and characterization of two sub-Neptunes in close orbits, as well as a tentative outer planet of a similar size, orbiting TOI-1260 – a low metallicity K6 V dwarf star. Photometry from Transiting Exoplanet Survey Satellite ( TESS ) yields radii of R b = 2.33 ± 0.10 and R c = 2.82 ± 0.15 R⊕, and periods of 3.13 and 7.49 d for TOI-1260 b and TOI-1260 c, respectively. We combined the TESS data with a series of ground-based follow-up observations to characterize the planetary system. From HARPS-N high-precision radial velocities we obtain M b = 8.6 _ - 1.5 ^ + 1.4 and M c = 11.8 _ - 3.2 ^ + 3.4 M⊕ . The star is moderately active with a complex activity pattern, which necessitated the use of Gaussian process regression for both the light-curve detrending and the radial velocity modelling, in the latter case guided by suitable activity indicators. We successfully disentangle the stellar-induced signal from the planetary signals, underlining the importance and usefulness of the Gaussian process approach. We test the system's stability against atmospheric photoevaporation and find that the TOI-1260 planets are classic examples of the structure and composition ambiguity typical for the 2–3 R⊕ range.